2022
DOI: 10.2174/1573402117666210218105338
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Uncontrolled Hypertension on the Longitudinal Systolic Function of the Left Ventricle

Abstract: Background: The assessment of the longitudinal component of left ventricular (LV) function is of major clinical importance for the early detection of LV contractile impairment. The aim of this study was to determine the impact of uncontrolled hypertension, on LV longitudinal systolic performance. Methods: The study population included 400 hypertensive patients: 271 patients with uncontrolled blood pressure (BP) and 112 without controlled BP, all patients underwent a complete ultrasound evaluation with calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…This may be because myocardial interstitial fibrous tissue hyperplasia and rearrangement of myocardial fibers were more obvious, leading to a more significant decline in myocardial strain function 11 . The research of Bendiab 12 and Kouzu et al 13 also confirmed the above views.…”
Section: Discussionmentioning
confidence: 81%
“…This may be because myocardial interstitial fibrous tissue hyperplasia and rearrangement of myocardial fibers were more obvious, leading to a more significant decline in myocardial strain function 11 . The research of Bendiab 12 and Kouzu et al 13 also confirmed the above views.…”
Section: Discussionmentioning
confidence: 81%
“…Indeed, weight loss has been reported to improve cardiac structure and function of patients with overweight [ 23 ]. Accordingly, effective and optimal treatment of HBP should be obtained in very high risk hypertensive patients such as those with T2DM [ 24 ]. In addition, antihypertensive drugs such as angiotensin-converting enzyme inhibitors, as observed in the present study, may have direct protective effects, and their use may contribute to reduced vascular complications in patients with HBP and concomitant T2DM [ 25 ].…”
Section: Discussionmentioning
confidence: 99%